Post-operative Right Ventricular Failure After Cardiac Surgery: A Cohort Study - Levy, David; Laghlam, Driss; Estagnasie, Philippe; Brusset, Alain; Squara, Pierre; Nguyen, Lee S. (Frontiers in Cardiovascular Medicine, 2021)
Introduction. Right ventricular failure (RVF) after cardiac surgery is an important risk factor of morbidity and mortality. Its diagnosis is challenging and thus, its incidence and predictors are not well-established. We investigated incidence, complications, and variables associated with clinically relevant postoperative RVF. Methods. We included all patients who underwent cardiac surgery with cardiopulmonary bypass, between 2016 and 2019 in a cardiac surgery center with standardized diagnostic and therapeutic management of RVF. RVF was considered only if clinically relevant: associated with hemodynamic instability requiring catecholamine support and inhaled nitric oxide relayed by sildenafil. Results. Overall, 3826 patients were included, of whom, 110 (2.9%) developed postoperative RVF. Mortality was not different among patients who developed postoperative RVF, compared to the rest of the cohort (1.8% vs. 0.7%, p = 0.17). Using a composite outcome which combined death, reintubation, stroke and prolonged ICU stay (more than 14 days) yielded an incidence of 6.6% and RVF was associated with this composite outcome with an odds-ratio of 3.6 (2.2-5.8), p<0.001. In a multivariable model, preoperative variables independently associated with postoperative RVF were: preoperative atrial fibrillation (adjusted odds-ratio (adjOR) 3.22 (95% confidence interval (95CI)=1.94-5.36), p<0.001), left ventricle ejection fraction below 50% (adjOR=2.55 (95CI=1.52-4.33), p<0.001), systolic pulmonary artery pressure above 55 mmHg (adjOR=8.64 (95CI=5.27-14.1); p<0.001, mitral valve surgery (adjOR=2.17 CI (95CI=1.28-3.66), p=0.004) and tricuspid valve surgery (adjOR=10.33 (95CI=6.14-17.4), p<0.001). In patients who developed postoperative RVF requiring treatment, 32 (29.1%) showed RV dysfunction before surgery. Conclusion. In this cohort study, 2.9% patients developed clinically significant postoperative RVF. Moreover, RVF was associated with severe adverse outcomes including death, strokes, reintubation and prolonged ICU stay.